EFFECT OF TIME AND DEPTH IMMERSION WITH SEAWATER ON COMPRESSIVE STRENGTH OF HIGH-QUALITY CONCRETE - Anisah Nur Fadhilah; Qomariah Qomariah; Nawir Rasidi (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2024)
The use of concrete on land and around the sea has different treatments, which affect the strength of concrete. In carrying out concrete treatment, pay attention to not only the quality of the water used but also the time and depth of the concrete immersion to produce good quality concrete. This study aims to determine the effect of immersion time and depth using fresh water and seawater on the concrete of compressive strength and to obtain the most optimal depth and time with seawater immersion. The quality of the concrete plan is 42 MPa with cylinder samples with a diameter of 15 cm and a height of 30 cm as many as 70 samples. Immersion is carried out with a treatment duration of 21 days, 28 days, and 56 days with variations in immersion depths of 0, 1/3h, 1/2h, and h. The data needed for this study are the results of compressive strength testing and absorption testing results on concrete, The immersion method used in this study is the water curing method. The research process carried out is by testing the physical properties of aggregates, calculating mix design and material requirement analysis, making test objects and testing fresh concrete, carrying out concrete treatment with water curing immersion methods with fresh water and seawater, conducting absorption and compressive strength testing, and analyzing data. The results showed that the compressive strength of concrete with differences in depth and time using seawater greatly affects the strength of concrete so that it produces higher compressive strength compared to fresh water. This hypothesis is caused by alkaline conditions that can strengthen the reaction of Ca (OH) 2, the formation of Friedel salts in concrete due to chloride content in seawater, and the influence of Sika Viscocrete 3115 N which can withstand carbonation in concrete. So based on all results, concrete with the most optimal seawater immersion at a depth of 1/2h with immersion for 56 days is 73.56MPa with a percentage increase of 19% compared to freshwater immersion.